Susceptibility of Brazilian maize landraces to the attack of Sitophilus zeamais (Coleoptera: Curculionidae). (September 2020) - Brilinger, Dahise; Wille, Cleiton Luiz; Machado da Rosa, Joatan; Franco, Cláudio Roberto; Carissimi Boff, Mari Inês
Abstract: Landraces are used in breeding programs as a source of resistance and compose a small group of genetic materials accepted under organic seed production. The goal of this study was to evaluate the susceptibility of Brazilian landraces grains to the attack of Sitophilus zeamais . Ten different landraces were subjected to the attack of S. zeamais in choice and no-choice experiments. We evaluated the number of emerged insects and the weight reduction of the damaged grains. The Presidente Amarelo landrace received 4.4 and 5.4 times less insects than Colorado and Cateto in the choice experiment. Also, the Ligeirinho and Presidente Amarelo landrace provided the emergence of 4.2 times less adults than Cateto. The landraces presented different results when submitted to choice and no-choice experiments. However, Cateto grains presented the highest susceptibility to attack in both experiments. Presidente Amarelo, on the other hand, presented the highest resistance to the attack of S. zeamais and so might be considered to be used as a source of resistance in breeding programs. Highlights: The exposure time did not affect S. zeamais selection of a landrace. The number of emerged insects differed across the evaluated landraces. Presidente Amarelo landrace presented the highest resistance to the attack of S. zeamais . Cateto landrace was the least susceptible in the choice experiment and might be considered in a push-pull farming system.